A case of neuro retinitis in association with COVID-19 - Asmita Mahajan; Swati Phuljhele; Rebika Dhiman (Indian Journal of Ophthalmology, 2022)
A 36-year-old female presented with blurring of vision in one eye for 10 days after 1 month of an episode of COVID-19 infection. Her fundus showed disc edema with blurring of margins along with exudation around the fovea. Her C-reactive protein levels were raised. She responded well to oral steroids. A likely association with COVID-19 infection and its associated immune response was suspected.